Undernutrition risk and obesity increase the risk of osteosarcopenia in Mexican adults aged 50 and over: a prospective cohort study - Omaña-Guzmán, Isabel; Kammar-García, Ashuin; Gutierrez-Robledo, Luis Miguel; Rosas-Carrasco, Oscar (Frontiers in Nutrition, 2025)
IntroductionUndernutrition risk in adults is a common but undiagnosed condition, while obesity is highly prevalent in this population. Osteosarcopenia is the coexistence of sarcopenia and osteopenia/osteoporosis and is related to higher morbidity and mortality. Undernutrition has been identified as an associated factor of osteosarcopenia; however, it is unknown whether undernutrition risk is also related to this condition. On the other hand, obesity has been associated with osteosarcopenia, and several biological mechanisms in the relationship between muscle, bone, and fat have been identified. However, in both cases, there is a lack of longitudinal studies that allow evaluation of whether these conditions precede and increase the risk of osteosarcopenia. Therefore, the objective was to evaluate the association between undernutrition risk and obesity with osteosarcopenia among Mexican community-dwelling adults aged 50 and over.MethodsThis is a secondary longitudinal study from the FraDySMex cohort. We considered data from 2014 and 2015 as baseline evaluations and 2019 as the follow-up evaluation. Undernutrition risk was assessed using the Mini Nutritional Assessment, obesity was assessed based on body fat percentage measured by DXA, and osteosarcopenia was diagnosed according to the FNIH criteria. To evaluate the association of obesity and undernutrition risk, we estimated mixed-effects logistic regression models. The final model was adjusted for sex, age, comorbidity, education, physical activity, and cognitive impairment.ResultsA total of 304 participants with two evaluations (baseline and follow-up) were included in the study. The baseline mean age of participants was 69.6 years (SD 9.1), with ages ranging from 50 to 92 years. Most of the participants were female (83.2%), 40% had between 7 and 12 years of education, and almost half were categorized as sedentary (47.8%) at baseline evaluation. Both undernutrition risk and obesity increased the risk of osteosarcopenia, with an OR of 2.24 (95% CI: 1.20–4.19) and an OR of 2.22 (95% CI: 1.17–4.23), respectively.ConclusionOur findings suggest that undernutrition risk, on the one hand, and obesity, on the other hand, can precede and increase the risk of osteosarcopenia in community-dwelling adults aged 50 and over.